Muhammadiyah dan Tuntunan Menuju Keluarga Sakinah - Alfiannor Alfiannor (Jurnal Budi Pekerti Agama Islam, 2024)
The concept of Sakinah Family, introduced by Aisyiyah since 1985, is a significant paradigm in realizing a harmonious and prosperous family both in this world and the hereafter. This article aims to discuss how Muhammadiyah, through Aisyiyah, formulates the Sakinah Family development program with strategies, approaches, and evaluations tailored to local conditions and the target age of the development. This research employs a qualitative approach with analysis of relevant literature. The findings highlight the importance of Sakinah Family development in building families that gain Allah's blessings and nurturing affection among family members. Aisyiyah develops principles such as divine orientation, extended family patterns, egalitarian relationships, and fulfilling the needs of worldly and hereafter well-being. This development encompasses spiritual, educational, economic, health, social, and environmental aspects. Collaboration with various parties such as UNICEF and BKKBN demonstrates Aisyiyah's commitment to enhancing family welfare in Indonesia. Collaborative programs cover various aspects such as maternal and child health, family planning, and social welfare, implemented at national and regional levels. Through these efforts, Aisyiyah contributes to creating Sakinah, Mawaddah, and Rahmah families.